Online assessment of suicide stigma, literacy and effect in Australia's rural farming community - Alison J. Kennedy; Susan A. Brumby; Vincent Lawrence Versace; Tristan Brumby-Rendell (BMC, 2018)
Abstract Background In Australia, farming populations have been identified as having higher rates of suicide, in comparison to metropolitan, rural and regional communities. The reasons for this are unclear although stigma is considered a risk factor. This study was designed to understand the role of suicide stigma and suicide literacy and the relationship between these. Methods A mixed-methods online intervention was developed. This paper reports on baseline quantitative data (suicide stigma, suicide literacy and suicide effect) collected from male and female rural Australian participants (N = 536) with an experience of suicide. Results When compared with previous Australian community samples, our sample demonstrated higher levels of stigma and higher levels of suicide literacy. Males were more likely to have considered suicide than females. Females were more likely than males to report a devastating and ongoing effect of suicide bereavement, but less likely than a previous Australian community sample. Conclusion Results of this study reiterate the need for improved understanding of the risk factors and experience of suicide within the context of life and work in rural Australian farming communities and how 'best practice' can be adapted to improve stigma reduction and suicide prevention efforts. Trial registration This research project was registered with the Australian New Zealand Clinical Trials Registry (ANZCTR) (ACTRN12616000289415) on 7th March, 2016.